Systematic review and rationale of using psychedelics in the treatment of cannabis use disorder - Phan, Angela N.; Terry, Garth E. (Frontiers in Psychiatry, 2023)
Introduction Cannabis use disorder (CUD) is prevalent in ~2–5% of adults in the United States and is anticipated to increase as restrictions to cannabis decrease and tetrahydrocannabinol (THC) content in cannabis products increase. No FDA-approved medications for CUD are currently available, despite trials of dozens of re-purposed and novel drugs. Psychedelics have garnered interest as a therapeutic class in other substance use disorders, and self-report surveys suggest they may result in positive outcomes for CUD. Herein, we review the existing literature pertaining to psychedelic use in persons with or at risk for CUD and consider the potential rationale underpinning psychedelics as a treatment for CUD. Methods A systematic search was performed in several databases. Inclusion criteria were primary research reporting use of psychedelics or related substances and CUD for treatment in human subjects. Exclusion criteria were results including psychedelics or related substances without changes in cannabis use or risks associated with CUD. Results Three hundred and five unique results were returned. One article was identified using the non-classical psychedelic ketamine in CUD; three articles were identified as topically relevant based on their secondary data or consideration of mechanism. Additional articles were reviewed for purposes of background, review of safety considerations, and formulating rationale. Conclusion Limited data and reporting are available on the use of psychedelics in persons with CUD, and more research is needed given the anticipated increase in CUD incidence and increasing interest in psychedelic use. While psychedelics, broadly, have a high therapeutic index with infrequent serious adverse effects, particular adverse effects at risk in the CUD population, such as psychosis and cardiovascular events, should be considered. Possible mechanisms by which psychedelics have therapeutic potential in CUD are explored.